2020
DOI: 10.3389/fchem.2020.615800
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Amplification in Soai's Asymmetric Autocatalysis by a Transient Stereodynamic Catalyst

Abstract: Mechanisms leading to a molecular evolution and the formation of homochirality in nature are interconnected and a key to the underlying principles that led to the emergence of life. So far proposed mechanisms leading to a non-linear reaction behavior are based mainly on the formation of homochiral and heterochiral dimers. Since homochiral and heterochiral dimers are diastereomers of each other, the minor enantiomer is shifted out of equilibrium with the major enantiomer by dimer formation and thus a reaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…33 1 H NMR experiments further proved the strong propensity of pyrimidylaldehydes to form hemiacetals. 44 Finally, extensive kinetic modelling allowed prediction of very strong chiral amplification and of the time of the inflection point as a function of initiator ee. 34,35 For simplicity, the autocatalytic cycle of the (R)-enantiomer has been omitted.…”
Section: The Denmark Proposal: Alkoxide Tetramer Through Zn-n Coordin...mentioning
confidence: 99%
“…33 1 H NMR experiments further proved the strong propensity of pyrimidylaldehydes to form hemiacetals. 44 Finally, extensive kinetic modelling allowed prediction of very strong chiral amplification and of the time of the inflection point as a function of initiator ee. 34,35 For simplicity, the autocatalytic cycle of the (R)-enantiomer has been omitted.…”
Section: The Denmark Proposal: Alkoxide Tetramer Through Zn-n Coordin...mentioning
confidence: 99%
“…Much more than a simple curiosity of nature, it is essential for the exceptional efficiency in information transfer, catalysis, and electron transfer of today’s biomolecules and confers directionality to molecular and cellular motion. Hence, homochirality is likely to play an important role in the emergence of function in the transition from chemistry to biology. ,, How biological homochirality arose from a (close to) racemic world is thus a question that intrigues. In the past decades, the scientific community has devoted much effort to study chiral amplification and symmetry breaking processes. , Most of these efforts have been directed at the polymerization of peptides and oligonucleotides, crystallization, , and asymmetric autocatalysis of small molecules, of which the Soai reaction is a famous example. An overview of these systems is provided in and . In many instances, autocatalysis plays an important role in the emergence of homochirality.…”
Section: Introductionmentioning
confidence: 99%
“…Besides Soai and coworkers, [9][10][11] the groups of Blackmond, 12 Brown et al, 13,14 and Amedjkouh et al [15][16][17] focused on the elucidation of the Soai reaction by experimental investigations. 18 Recent mechanistic investigations by the groups of Denmark 19,20 and Trapp 21,22 proposed two different mechanistic approaches. 23 In 2020, Denmark et al proposed a homochiral tetramer in a square-macrocycle-square conformation of the product alkoxide as catalytically active species in the Soai reaction.…”
Section: Introductionmentioning
confidence: 99%
“…23 In 2020, Denmark et al proposed a homochiral tetramer in a square-macrocycle-square conformation of the product alkoxide as catalytically active species in the Soai reaction. 21,22 Trapp et al proposed a different mechanism for the Soai reaction, based on identified hemiacetalate complexes, which are formed from the aldehyde and Zn-alkoxide. The configuration of the Znalkoxides determines the configuration of the newly formed stereogenic center of the hemiacetalate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation